Experimental Study on Low-Strength Similar-Material Proportioning and Properties for Coal Mining - Shaojie Chen; Hailong Wang; Junwen Zhang; Huilin Xing; Huaiyuan Wang (Advances in Materials Science and Engineering)
Similar-material simulation test is an effective tool to study the practical problems in mining and civil engineering. This paper conducts an orthogonal study on low-strength similar materials comprising sand, fly ash, and plaster and analyses the sensitivity of the materials. The mechanical properties of the similar materials strongly depend on the proportioning ratio, and they can satisfy different similar-material simulation tests. The compression strength and elastic modulus of the similar material decrease as the sand-binder ratio or cement ratio increases. There are approximately linear relations between the compression strength/elastic modulus and sand-binder ratio and approximately power relations between the compression strength/elastic modulus and sand-binder ratio. Sensitivity analysis employing the range method shows that the effects of the cement ratio on the compression strength and elastic modulus are more obvious than the effects of the sand-binder ratio. Finally, one of similar materials is used in a simulation test of coal backfill mining.